PENGARUH STRUKTUR KEPEMILIKAN DAN LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN RITEL DI INDONESIA - Fauziyah Nafishah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Fauziyah Nafishah; This study aims to determine the effect of managerial ownership, and leverage on stock returns in retail companies in Indonesia.The research method used in this study is a quantitative method, the independent variable used in this study consists of managerial ownership structure and leverage while the dependent variable is stock returns. The population in this study are retail companies listed on the Indonesia Stock Exchange (IDX) listed on the Indonesia Stock Exchange 2013-2017 period. Sample selection through purposive sampling method. There are 7 (seven) companies that have criteria as research samples, so that the research data totaled 35 data. Data collection techniques used are document review, the data analyzed are annual financial reports (annual report), previous research journals and other literature relating to research problems. Data processing and analysis techniques include financial management analysis, multiple linear regression analysis, classic assumption test, hypothesis test, coefficient of determination test and coefficient of determination test. The results showed that managerial ownership partially influential and significant on stock returns, and partial leverage had no significant and significant effect on stock returns. While simultaneously managerial ownership, and leverage affect stock returns.Therefore, it is better for the company's internal parties to improve the company's performance because the company's performance and good company production will make investors interested in investing in these companies. Keyword : managerial ownership, leverage, stock returns